2011
DOI: 10.1017/s1041610211001591
|View full text |Cite
|
Sign up to set email alerts
|

Daily hassles, physical illness, and sleep problems in older adults with wishes to die

Abstract: Since desire for death is the first step into the suicidal process, health professionals should seriously consider the important and unique contribution of these variables in order to have more opportunities for detection and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 35 publications
5
58
0
3
Order By: Relevance
“…Kanner and colleagues found that daily hassles predicted current and subsequent psychological symptoms, such as, depression and anxiety, more accurately than significant negative life events (Kanner et al, 1981). Later empirical work has also found that stress sensitivity to daily hassles was significantly associated with, dissatisfaction with current life circumstances (Lavee & Ben-Ari, 2008), marital problems (Harper, Schaalje & Sandberg, 2000), reactive cocaine use in individuals with cocaine dependency (Waldrop et al, 2007) and, importantly, the wish to die in older adults (Boyer et al, 2012) and heightened stress-sensitivity in people with bipolar disorder with more frequent depressive episodes (Havermans & Nicolson, 2007). The current finding points towards the need to assess the individual"s interpretation or personal meaning attached to more 'every day' events and formulating strategies to help people cope with the impact of such events.…”
Section: Discussionmentioning
confidence: 99%
“…Kanner and colleagues found that daily hassles predicted current and subsequent psychological symptoms, such as, depression and anxiety, more accurately than significant negative life events (Kanner et al, 1981). Later empirical work has also found that stress sensitivity to daily hassles was significantly associated with, dissatisfaction with current life circumstances (Lavee & Ben-Ari, 2008), marital problems (Harper, Schaalje & Sandberg, 2000), reactive cocaine use in individuals with cocaine dependency (Waldrop et al, 2007) and, importantly, the wish to die in older adults (Boyer et al, 2012) and heightened stress-sensitivity in people with bipolar disorder with more frequent depressive episodes (Havermans & Nicolson, 2007). The current finding points towards the need to assess the individual"s interpretation or personal meaning attached to more 'every day' events and formulating strategies to help people cope with the impact of such events.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 A number of studies have demonstrated that insomnia is strongly associated with suicidal ideation cross-sectionally 8,9,10 and longitudinally, 11,12 even when controlling for hopelessness and depression. 13 Furthermore, several studies have established a link between insomnia and death by suicide among adolescents, 14 adults, 15 and older adults, 16 underscoring insomnia as a critical risk factor for suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Death thoughts and wishes to die are the first steps of a process that can proceed to suicidal ideation, suicide attempts or even death by suicide. These are all generally known as suicidal behaviours [6].…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation to these changes is not always easy, possibly increasing the risk for suicidal behaviours [6]. Therefore, it is important to identify some modifiable risk factors, in order to prevent suicide in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation